The corepressor Atrophin specifies odorant receptor expression in Drosophila. - Alkhori, L.; Ost, A.; Alenius, M. (FASEB Journal (Federation of American Societies for Experimental Biology), 2014)
In both insects and vertebrates, each olfactory sensory neuron (OSN) expresses one odorant receptor (OR) from a large genomic repertoire. How a receptor is specified is a tantalizing question addressing fundamental aspects of cell differentiation. Here, we demonstrate that the corepressor Atrophin (Atro) segregates OR gene expression between OSN classes in Drosophila. We show that the knockdown of Atro result in either loss or gain of a broad set of ORs. Each OR phenotypic group correlated with one of two opposing Notch fates, Notch responding, Nba (N(on)), and nonresponding, Nab (N(off)) OSNs. Our data show that Atro segregates ORs expressed in the Nba OSN classes and helps establish the Nab fate during OSN development. Consistent with a role in recruiting histone deacetylates, immunohistochemistry revealed that Atro regulates global histone 3 acetylation (H3ac) in OSNs and requires Hdac3 to segregate OR gene expression. We further found that Nba OSN classes exhibit variable but higher H3ac levels than the Nab OSNs. Together, these data suggest that Atro determines the level of H3ac, which ensures correct OR gene expression within the Nba OSNs. We propose a mechanism by which a single corepressor can specify a large number of neuron classes.